2021
DOI: 10.1001/jamanetworkopen.2021.34147
|View full text |Cite|
|
Sign up to set email alerts
|

Disparities in COVID-19 Outcomes by Race, Ethnicity, and Socioeconomic Status

Abstract: IMPORTANCE COVID-19 has disproportionately affected racial and ethnic minority groups, and race and ethnicity have been associated with disease severity. However, the association of socioeconomic determinants with racial disparities in COVID-19 outcomes remains unclear.OBJECTIVE To evaluate the association of race and ethnicity with COVID-19 outcomes and to examine the association between race, ethnicity, COVID-19 outcomes, and socioeconomic determinants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
395
7
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 537 publications
(435 citation statements)
references
References 94 publications
31
395
7
2
Order By: Relevance
“…Patients of Black, Hispanic and South Asian origin also have a higher case fatality rate. Inequitable access to healthcare is at least partly responsible for these ethnic differences ( 10 , 11 ).…”
Section: Patients At Increased Riskmentioning
confidence: 99%
“…Patients of Black, Hispanic and South Asian origin also have a higher case fatality rate. Inequitable access to healthcare is at least partly responsible for these ethnic differences ( 10 , 11 ).…”
Section: Patients At Increased Riskmentioning
confidence: 99%
“…Nevertheless, on this final point, diagnosis of myocardial injury is based on clinical, EKG, laboratory, and imaging data and coronary angiography is often not required to make this diagnosis. While some authors [ 23 ] have suggested a racial predisposition to adverse outcomes from COVID-19, the present study could not study the effect of race on mortality outcomes due to sample size limitations. Such data was also not available for meta-analysis.…”
Section: Discussionmentioning
confidence: 84%
“…The use of mAb is a safe and effective treatment for individuals with high-risk conditions for disease progression. Age over 65 (Odd ratio:6.01), Hispanic race (Odds Ratio: 1.35), diabetes mellitus (Odd Ratio: 3.68), coronary artery disease (Odds Ratio: 3.23), and obesity (Odds Ratio: 4.17) have been associated with increased risk of progression to severe illness [10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%